2002
DOI: 10.1128/jb.184.23.6417-6423.2002
|View full text |Cite|
|
Sign up to set email alerts
|

The rpoZ Gene, Encoding the RNA Polymerase Omega Subunit, Is Required for Antibiotic Production and Morphological Differentiation in Streptomyces kasugaensis

Abstract: The occurrence of pleiotropic mutants that are defective in both antibiotic production and aerial mycelium formation is peculiar to streptomycetes. Pleiotropic mutant KSB was isolated from wild-type Streptomyces kasugaensis A1R6, which produces kasugamycin, an antifungal aminoglycoside antibiotic. A 9.3-kb DNA fragment was cloned from the chromosomal DNA of strain A1R6 by complementary restoration of kasugamycin production and aerial hypha formation to mutant KSB. Complementation experiments with deletion plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Given the role identified for v in mediation of the effects of alarmone ppGpp on RNAP, the defective execution of stringent response signals for biofilm formation due to lack of v subunit in RNAP can be conceived as a possible explanation for the phenotypes we observed for mcdrz. This will be similar to the explanation that has been offered for another surprising connection observed for the v subunit: with antibiotic production and morphogenesis in Streptomyces kasugaensis (Kojima et al, 2002).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Given the role identified for v in mediation of the effects of alarmone ppGpp on RNAP, the defective execution of stringent response signals for biofilm formation due to lack of v subunit in RNAP can be conceived as a possible explanation for the phenotypes we observed for mcdrz. This will be similar to the explanation that has been offered for another surprising connection observed for the v subunit: with antibiotic production and morphogenesis in Streptomyces kasugaensis (Kojima et al, 2002).…”
Section: Discussionsupporting
confidence: 83%
“…However, evidence regarding a functional role played by v has been rare in the literature. The finding that a mutation in the rpoZ gene encoding v caused pleiotropic phenotypes in Streptomyces kasugaensis was suggestive of functions which required to be further defined (Kojima et al, 2002). A more direct indication has been the recent confirmation of the requirement of the v subunit for the response of RNAP to ppGpp (Vrentas et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…are positively controlled by ppGpp (Bibb 2005). Disruption of rpoZ drastically disrupts these processes in Streptomyces kasugaensis (Kojima et al 2002), suggesting that the effects of ppGpp on RNAP in this organism are dependent on in vivo, perhaps by the same mechanism described here for E. coli.…”
Section: Additional Roles For In Vivomentioning
confidence: 61%
“…We previously cloned a 22.4-kb chromosomal DNA region (kas cluster) containing the biosynthetic genes for KSM together with kac 338 the KSM acetyltransferase gene, kasKLM, ABC transporter genes, both of which are responsible for KSM self-resistance, and kasT, the KSM-biosynthesis-specific transcriptional activator gene [6][7][8][9]. Meanwhile, we found that disruption of rpoZ, the gene encoding the RNA polymerase (RNAP) subunit omega (w), turned the wild-type S. kasugaensis into pleiotropic mutants, which were phenotypically similar to the bldA mutation, and clarified that the gene is required for KSM production and aerial mycelium formation in the streptomycete [10] Antibiotic-producing streptomycetes generally harbor the selfresistance gene within the biosynthetic gene cluster, and a variety of such clusters have been cloned using the self-resistance genes as probe [4] . In a similar attempt, we initially cloned a 7.6-kb Pstl-Kpnl DNA fragment, including the KSM acetyltransferase gene (kac338) and eight genes (kasA-kasl) as illustrated in Figure. 4, from the chromosomal DNA of wild-type S. kasugaensis [7] .…”
Section: Introductionmentioning
confidence: 84%